2001
DOI: 10.1002/jez.1027
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and age‐related changes in blood parasite prevalence in dark‐eyed juncos (Junco hyemalis, Aves, Passeriformes)

Abstract: We determined seasonal changes in blood parasite infections in a free-living population of Dark-eyed Juncos (Junco hyemalis) breeding in interior Alaska (65 degrees N; 148 degrees W). The common parasites found in blood smears were Leucocytozoon fringillinarum (56%), Trypanosoma avium (33%), and Haemoproteus fringillae (9%). In males, parasite prevalences were relatively high at arrival on breeding grounds and increased during the breeding season. Intensity of infection with Leucocytozoon also increased betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
61
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 57 publications
5
61
2
Order By: Relevance
“…The increase in prevalence with age could be explained by higher mortality of young birds (Valkiūnas 2005), deterioration in the immune function of adults (Cichoñ et al 2003), or increased exposure to the vectors (Ahmed and Mohammed 1978). Several authors have confirmed the relationship between host body weight and prevalence of blood parasites (Scheuerlein andRicklefs 2004, Marzal et al 2008), but this effect is not always present and similarly to our study, other past studies have reported no direct relationship between the occurrence of blood parasites and host body weight (Hauptmanová et al 2002, Deviche et al 2001, Palinauskas et al 2005. Clarification of this relationship is often complicated in wildlife field studies due to many uncontrolled variables (Madsen et al 2007).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The increase in prevalence with age could be explained by higher mortality of young birds (Valkiūnas 2005), deterioration in the immune function of adults (Cichoñ et al 2003), or increased exposure to the vectors (Ahmed and Mohammed 1978). Several authors have confirmed the relationship between host body weight and prevalence of blood parasites (Scheuerlein andRicklefs 2004, Marzal et al 2008), but this effect is not always present and similarly to our study, other past studies have reported no direct relationship between the occurrence of blood parasites and host body weight (Hauptmanová et al 2002, Deviche et al 2001, Palinauskas et al 2005. Clarification of this relationship is often complicated in wildlife field studies due to many uncontrolled variables (Madsen et al 2007).…”
Section: Discussionsupporting
confidence: 76%
“…Similarly to the results of Svobodová and Votýpka (1998), we have also recorded a higher infection intensity in adult birds than in subadults. Some studies have presented the opposite result for L. fringillinarum (Allander and Bennett 1994) or no significant relationship between haemoparasite prevalence and age of birds (Deviche et al 2001).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, a number of previous studies also reported an increase in prevalence with age (e.g. Weatherhead and Bennett 1991;Norris et al 1994;Seutin 1994;Deviche et al 2001). We did not find any effect of sex on infection status, when considering either pooled infections or infections with separate lineages (pTURDUS1, hPARUS1).…”
Section: Discussionmentioning
confidence: 52%
“…If infection causes a decrease in health a decrease in all hematological parameters is to be expected in the breeding season. It has been postulated that seasonal variation in hemoparasite prevalence is related to intrinsic factors of the reproductive cycle (BENNETT et al 1982, DEVICHE et al 2001, GARVIN & GREINER 2003. This occurs because the greater effort and energy demands of the reproductive period conflicts with the energy necessary to maintain the or- ganism, compromising the immune system and individual health.…”
Section: Discussionmentioning
confidence: 99%